Integrating the 2I/E model into dimensional comparison theory: Towards a comprehensive comparison theory of academic self-concept formation. (August 2019) - Wolff, Fabian; Helm, Friederike; Möller, Jens
Abstract: The 2I/E model describes academic self-concept formation by the joint operation of social, temporal, and dimensional comparisons. Dimensional comparison theory assumes that dimensional contrast effects are weaker between similar subjects than between dissimilar subjects. This research combined these two perspectives in two empirical studies: For the first time, we integrated four subjects (math, science/physics, English, German) into one generalized 2I/E model and compared dimensional comparison effects between dissimilar and similar subjects, while controlling for social and temporal comparison effects. In line with the 2I/E model, we found strong social, small temporal, and small to moderate dimensional comparison effects on students' subject-specific self-concepts. In line with dimensional comparison theory, the dimensional contrast effects were substantially weaker, and sometimes even assimilative, between similar compared to dissimilar subjects. We discuss these findings with respect to the integration of the 2I/E model into dimensional comparison theory and possibilities for teachers to foster students' self-concepts. Highlights: 2I/E model valid when four subjects integrated into the model. Social comparison effects strong; temporal comparison effects small. Dimensional contrast effects small to moderate between dissimilar subjects. Dimensional contrast effects significantly weaker between similar subjects. Effects of achievement changes on noncorresponding self-concepts close to zero.